SEMIOTIC ANALYSIS OF RELIGIOUS SCENES IN THE FILM "SURAT KECIL UNTUK TUHAN" - Melisa Naibaho; Nurhanifah Nurhanifah (Journal Analytica Islamica, 2025)
This study aims to examine the symbolic meanings within religious scenes in the film Surat Kecil untuk Tuhan (A Little Letter to God) using Roland Barthes' semiotic approach. The film, based on the true story of a teenage girl named Keke who suffers from cancer, presents various religious symbols such as prayer, places of worship, a letter to God, and other spiritual expressions. The analysis is conducted through three levels of meaning: denotative (literal meaning), connotative (emotional and cultural meaning), and myth (ideological meaning). The findings reveal that these religious symbols are not merely decorative visual elements but serve as powerful conveyors of spiritual messages about faith, hope, sacrifice, and tolerance. The film effectively constructs a touching and humanistic religious narrative, offering viewers a medium for reflection on the values of life and spirituality.